BROKEN FAMILY STRUCTURES AND THEIR EDUCATIONAL IMPLICATIONS: A REVIEW OF SOCIO-EMOTIONAL AND ACADEMIC DEVELOPMENT IN STUDENTS - Cynthia Petra Haumahu; Criezta Korlefura; Theophanny P. Th. Rampisela (Adisam Publisher, 2026)
Broken family structures have become an increasingly important issue in contemporary education, as they influence students’ socio-emotional development and academic achievement. Family instability caused by parental separation, divorce, conflict, neglect, and dysfunctional parenting environments may create emotional distress and educational difficulties among students. This study aims to examine the educational implications of broken family structures by reviewing the relationships among parenting styles, social support, socio-emotional development, and academic achievement. The research employed a qualitative library research method using scholarly articles, books, and reputable international journals indexed in Scopus and other academic databases published primarily within the last five years. The collected data were analyzed using content analysis and thematic synthesis to identify major conceptual patterns and recent research findings regarding students from broken-home families. The findings indicate that broken family structures significantly affect students’ emotional stability, self-esteem, motivation to learn, classroom participation, and academic performance. Students experiencing family instability are more vulnerable to anxiety, depression, emotional insecurity, and behavioral problems that interfere with educational engagement. However, supportive parenting styles, positive school environments, peer relationships, and counseling support systems function as protective factors that strengthen students’ resilience and adaptability. This study also highlights the importance of trauma-informed and inclusive educational approaches in supporting students from vulnerable family backgrounds. The novelty of this research lies in its integrative perspective, which combines socio-emotional, academic, parenting, and social support dimensions within a unified educational framework. Therefore, collaboration among families, schools, communities, and policymakers is essential to create supportive educational ecosystems that promote students’ emotional well-being and academic success despite family adversity.